Determinants of Asset Utilization of Yogyakarta Special Region Government - Sri Suharsih; I Ketut Nama; Rini Dwi Astuti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
Regional assets are an essential resource for local governments as the primary support for local revenue. Therefore, local governments must be able to manage assets adequately. The variables that affect the probability of using local government assets in the Special Region of Yogyakarta are population density and health facilities. Variables of land area, GRDP, and educational facilities have not increased the probability of asset utilization in the Special Region of Yogyakarta. The various problems and challenges faced in asset management must be addressed immediately by carrying out reforms in regional government asset management.